Negotiating Religion, State, and Custom: Islamic Values in the Malay Merisik Pre-marital Tradition at Medan City - Muhammad Hafizh; Muhammad Yusuf Rangkuti; Muhammad Rizal Khoirul Umam; Ali Baroroh Al Muflih; Rahmi Amalia; Muhammad Fauzan Ni’ami (Al-Mazaahib: Jurnal Perbandingan Hukum, 2026)
The practice of merisik remains alive and continues to be preserved in the Malay customs of Medan, even though there are no explicit regulations regarding the merisik tradition in either Islamic law or state law. This article will discuss how the diversity of traditional wedding practices in Indonesia, specifically the merisik tradition among the Malay community in Medan, is negotiated within a multicultural context from the perspectives of Islam and customary law. The objective of this study is to identify Islamic values within the merisik tradition and to analyze their relevance to Malay customary law. This research employs a qualitative approach based on field research, utilizing data collection techniques such as interviews and observation, supported by secondary data from literature and Google Scholar journals over the past decade, which are analyzed using a descriptive-normative approach. The results of this study indicate that the merisik tradition reflects religious, personal, and social values that are closely linked to both Malay customary law and Islamic values. The main argument of this article centers on the negotiation between the merisik tradition and Islamic law and Malay customary law. This tradition has historical ties to the process of Islamization among the Malay community in Medan and embodies Islamic values, namely, religious (kafā’ah), personal (trustworthiness and honesty), and social (consultation, etiquette in visiting and hosting), which align with Malay customary law in fostering family harmony and social sustainability. Praktik mersik tetap hidup dan terus dilestarikan dalam adat Melayu Kota Medan meskipun tidak ada regulasi eksplisit mengenai tradisi merisik dalam hukum Islam maupun hukum negara. Artikel ini akan mendiskusikan bagaimana praktik keragaman adat pernikahan di Indonesia, khususnya tradisi merisik dalam masyarakat Melayu Kota Medan, yang dinegosiasikan dengan kondisi multikultural dari perspektif Islam dan hukum adat. Tujuan penelitian ini adalah mengidentifikasi nilai-nilai Islam dalam tradisi merisik serta menganalisis relevansinya dengan hukum adat Melayu. Riset ini menggunakan pendekatan kualitatif berbasis field research dengan teknik pengumpulan data melalui wawancara dan observasi, didukung data sekunder dari literatur dan jurnal Google Scholar dalam kurun waktu satu dekade terakhir, yang dianalisis secara deskriptif-normatif. Hasil penelitian ini menunjukkan bahwa tradisi merisik mencerminkan nilai-nilai keagamaan, pribadi, dan sosial yang erat kaitannya dengan hukum adat Melayu maupun nilai-nilai Islam. Argumentasi utama artikel ini terletak pada negosiasi tradisi merisik dengan hukum islam dan adat Melayu. Tradisi ini memiliki keterkaitan historis dengan proses Islamisasi masyarakat Melayu di Medan serta mengandung nilai Islam, yaitu religius (kafā’ah), kepribadian (amanah dan kejujuran), serta sosial (musyawarah, adab bertamu dan menjamu), yang selaras dengan hukum adat Melayu dalam membangun harmonisasi keluarga dan keberlanjutan sosial.